Cloud Computing Technology Setups to Support: The Learning Management System (LMS) in Higher Education Institutions in Oman - Alajmi, Qasim; Sadiq, Ali Safa (Waljat College of Applied Sciences, 2016)
The cloud computing terminology is used widely nowadays. Some people may not understand its technical meaning but they keep repeating this word every time an organisation is involved. The most crucial issue is to understand the in-depth meaning of the terminology, especially, for the decision makers in any company. Any misunderstanding would lead to wrong decision-making which can cost the organisation much time and resources. The internet is one of the most vital infrastructures needed to deploy this kind of technology which has become an important part of our lives. The author will explain in details the various types of Cloud computing services, such as; SaaS (Software as a Service), PaaS (Platform as a Service) and IaaS (Infrastructure as a Service). This paper will discuss in detail the challenges and security issues that exist in the implementing of cloud computing service in most of the higher education initiations in Oman. In general, this paper will allow the organisations to choose where, when, and how they use cloud computing, and help the decision makers to play the right role in higher education institutions